(untitled) (Research, Society and Development, 2020)
Several components of the fruit are part of its chemical composition, which give the characteristics of color and taste, in addition to the nutritional effects, which contribute to the consideration of the main sources of vitamins, minerals and fiber, necessary for the human diet. Moreover, with the full use of the fruits it is possible to reverse or minimize the situation the country faces, with people going hungry and tons of food being thrown in the garbage. The work aimed to elaborate flours of orange, melon and pineapple peel and characterize them as to chemical and colorimetric properties. The peels were dried in a greenhouse with air circulation, at a temperature of 60 ºC. After drying, they were crushed in an industrial blender and passed through a sieve. The flours obtained were characterized as to chemical parameters (total titratable acidity, total soluble solids content/°Brix and pH) and colorimetric, by means of the colorimeter and, from these values, the values of Chroma (C*) and tonal angle (h°) were calculated. Orange, melon and pineapple flours had acidity values above that allowed by current legislation. The orange and melon flours showed high luminosity, and the intensity of yellow excelled the red for all the flours produced.